INNOVATIONS IN ADHESIVES WITH LIGNIN NANOPARTICLES FOR BONDING IN THE WOOD INDUSTRY: A LITERATURE REVIEW - dos Santos, Carolina Aparecida; Brito, Flávia Maria Silva; Sousa, Thaís Brito; dos Santos, Laise de Jesus; Guimarães Neto, Rosalvo Maciel; Guimarães Junior, José Benedito (Seven Editora, 2026)
The growing concern for environmental sustainability and the need to reduce dependence on fossil resources have driven the search for more environmentally friendly materials in the timber industry. In this scenario, adhesives used in bonding wood and its derivatives play a central role, as they directly influence the performance, durability, and environmental impact of lignocellulosic panels and products. Traditionally, this industry employs synthetic adhesives based on petroleum derivatives, which exhibit excellent bonding efficiency and stability over time. However, the use of these materials is associated with the emission of volatile organic compounds, especially formaldehyde, in addition to issues related to the toxicity and environmental footprint of their production. Given these limitations, lignin has aroused increasing interest as a sustainable alternative for the development of new adhesive systems or for the modification of conventional formulations. Recent advances have shown that the conversion of lignin to the nanoscale significantly expands its application possibilities. Lignin nanoparticles exhibit a high surface area, better dispersion in the adhesive matrix, and greater availability of functional groups, favoring more efficient chemical and physical interactions. Incorporated into synthetic adhesives, they can contribute to increased mechanical strength, improved thermal stability, and greater moisture resistance, as well as positively influencing the adhesive’s curing kinetics. In this context, this chapter aims to present innovations related to the use of lignin nanoparticles in adhesives for bonding wood and its derivatives. DOI: https://doi.org/10.56238/sevened2026.008-096